Perancangan Website Profil Desa Kedungpapar sebagai Media Informasi Digital - Fatikhatun Nikmatus Sholihah; Achmad Sulthon Hadi; Cristian Sanggar Supriatno; Feriska Maharani; Syaifun Affandi; M. Ihsan Masrur (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The rapid development of information technology has significantly influenced community life, particularly in how information is obtained and disseminated. However, the dissemination of information in Kedungpapar Village has remained conventional, relying on notice boards and printed materials, resulting in limited accessibility and low transparency. This community service program aimed to design and develop a village profile website as a digital information medium. The website was built using the waterfall method through structured stages, including needs analysis, system design, implementation, testing, deployment, and maintenance. The results show that the website functions effectively as a digital communication tool by providing village profiles, potential resources, development programs, and interactive features for public feedback. The program has increased transparency in village governance, improved community participation, and strengthened the village’s digital identity. This initiative demonstrates that adopting information technology in rural governance can support e-government implementation and sustainable village development.